Validation of the 7‐item Functional Assessment of Cancer Therapy‐General (FACT‐G7) as a short measure of quality of life in patients with advanced cancer. Issue 16 (27th May 2020) - Mah, Kenneth; Swami, Nadia; Le, Lisa W.; Chow, Ronald; Hannon, Breffni L.; Rodin, Gary; Zimmermann, Camilla
Abstract : Background: Assessing quality of life is essential for individuals with advanced cancer, but lengthy assessments can be burdensome. The authors investigated the psychometric characteristics of the FACT‐G7, a 7‐item quality‐of‐life measure derived from the Functional Assessment of Cancer Therapy‐General (FACT‐G) scale, in advanced cancer. Methods: Data were obtained from outpatients with advanced cancer who were enrolled in a randomized controlled trial of early palliative care. At baseline, 228 intervention participants and 233 control participants (N = 461) completed the FACT‐G and measures of symptom severity, quality of life near the end of life, problematic medical communication, and satisfaction with care. Follow‐up measures were administered monthly for 4 months. Results: The FACT‐G7 showed good internal consistency (Cronbach α = .72‐.80), and its single‐factor structure was supported. It correlated strongly with the FACT‐G total, physical, and functional indices and with symptom severity (absolute r  = 0.73‐0.92); more moderately with the FACT‐G emotional index and with symptom impact and preparation for the end of life ( r  = .40‐.71); and least with the FACT‐G social/family index and with relationship with health care provider, life completion, problematic medical communication, and care satisfaction measures (absolute r  = .26‐.44). Eastern Cooperative Oncology Group performance status groups differed on FACT‐G7 scores, as expected (all P  < .001). Improvements in FACT‐G7 scores in the intervention group compared with the control group at 3‐month ( P  = .049) and 4‐month ( P  = .034) follow‐up supported responsiveness to change and somewhat greater sensitivity than the FACT‐G scores. Conclusions: The FACT‐G7 is a valid, brief measure particularly of the physical and functional facets of quality of life. It may enable rapid quality‐of‐life assessments in patients with advanced cancer. Abstract : Brief measures are needed for rapid, less burdensome quality‐of‐life assessment in patients with advanced cancer who are receiving palliative care. The Functional Assessment of Cancer Therapy‐General 7‐item scale (FACT‐G7) is a brief, cancer‐specific tool that demonstrates promising psychometric properties with this population and may be particularly sensitive to changes in quality‐of‐life domains relating to symptoms and physical functioning.